Rancang Bangun Sistem Enterprise Resource Planning Construction Sebagai Solusi Manajemen Proyek Konstruksi - Yudhistira, Aditya Septian; Sari, Nova Noor Kamala; Priskila, Ressa (Universitas Palangka Raya, 2023)
Construction management is a professional service that uses special project management techniques to oversee the course of construction projects from the initiation stage to project closure. Enterprise Resource Planning (ERP) is an information technology solution that enables businesses and their suppliers to manage large projects effectively and efficiently throughout the project life cycle. Proper utilization of internal and external resources is very important if a construction company wants to make the best business decisions, maximize business goals, and survive in a competitive environment, it requires a system that can integrate various business functions and resources, especially those related to project procedures. Thus, a system Enterprise Resource Planning Construction System as a Construction Management Solution is designed. This system was developed using the waterfall software development methodology, which consists of four stages. Among other things, analyzing and defining features, constraints and system objectives, conducting system design to form a system architecture based on predetermined requirements using UML, implementing and unit testing and performing system integration and testing. The result of this research is an Enterprise Resource Planning Construction system that integrates Invoicing, Customer Relationship Management, Sales, Purchase, Inventory, Human Resource and Project modules. So that this system can be an alternative construction project management solution for managing construction projects online.